Combining Immunotherapy and Radiotherapy for Cancer Treatment: Current Challenges and Future Directions - Wang, Yifan; Deng, Weiye; Li, Nan; Neri, Shinya; Sharma, Amrish; Jiang, Wen; Lin, Steven H. (Frontiers in Pharmacology, 2018)
Since the approval of anti-CTLA4 therapy (ipilimumab) for late-stage melanoma in 2011, the development of anticancer immunotherapy agents has thrived. The success of many immune-checkpoint inhibitors has drastically changed the landscape of cancer treatment. For some types of cancer, monotherapy for targeting immune checkpoint pathways has proven more effective than traditional therapies, and combining immunotherapy with current treatment strategies may yield even better outcomes. Numerous preclinical studies have suggested that combining immunotherapy with radiotherapy could be a promising strategy for synergistic enhancement of treatment efficacy. Radiation delivered to the tumor site affects both tumor cells and surrounding stromal cells. Radiation-induced cancer cell damage exposes tumor-specific antigens that make them visible to immune surveillance and promotes the priming and activation of cytotoxic T cells. Radiation-induced modulation of the tumor microenvironment may also facilitate the recruitment and infiltration of immune cells. This unique relationship is the rationale for combining radiation with immune checkpoint blockade. Enhanced tumor recognition and immune cell targeting with checkpoint blockade may unleash the immune system to eliminate the cancer cells. However, challenges remain to be addressed to maximize the efficacy of this promising combination. Here we summarize the mechanisms of radiation and immune system interaction, and we discuss current challenges in radiation and immune checkpoint blockade therapy and possible future approaches to boost this combination.